Mind-body-medicine and comprehensive lifestyle-modification in patients with Crohn's disease—Feasibility of a randomized controlled trial under pandemic circumstances - Bauer, Nina; Löffler, Claudia; Öznur, Özlem; Uecker, Christine; Keil, Thomas; Langhorst, Jost (Frontiers in Integrative Neuroscience, 2022)
Introduction Mind-body medicine (MBM) focuses on stress reduction and lifestyle changes. The primary objective of this pilot trial was to test study feasibility of a complex integrative MBM program for patients with Crohn's disease (CD), especially in rural regions, and under pandemic conditions. Methods Patients were stratified and randomized to the intervention group (IG) or the control group (CG). The intervention included a weekly 6-h session for 10 weeks. The CG (waiting list) received an initial 90-min workshop and started the intervention 9 months later. The primary outcome for study feasibility was recruitment and retention rates, as well as reasons for drop-out. The trial took place in Bamberg, Germany (September 2020 to December 2021). Results Totally 700 members of the German Crohn's and Colitis Organization—DCCV—were contacted. A total of 15% (102/700; 95% CI 12–17%) expressed interest to participate. Following screening, 41% (95% CI 32–50) were randomized to IG (n = 22) and CG (n = 20). The patients were on average (±standard deviation) 48 ± 13 years old, 67% were female, and have been suffering from CD for 20 ± 12 years. Patients traveled 71.5 ± 48.7 km (range: 9–227 km) to the intervention with no differences between IG and CG. At the 6-month follow-up, 36/42 (86%, 95% CI 74–95%) participants completed final assessment and 19/22 (86%, 95% CI 70–100%) the intervention. The most important reasons for non-responding were work-related (12/60; 20%) and for or drop-out pandemic-related anxiety (3/6). No patient and staff member became infected with SARS-CoV-2 during the study. Conclusion The feasibility of the MBM study was confirmed in terms of predefined recruitment and retention criteria, both despite difficult conditions (including the rural setting) and patients' fears associated with the pandemic. It was crucial to develop appropriate hygiene and safety concepts that enable chronically ill patients to participate in helpful group-based interventions even under pandemic conditions. Clinical trial registration ClinicalTrials.gov, identifier: NCT05182645.